Environmentally benign catalytic hydroformylation-oxidation route for naproxen synthesis - Rajurkar, Kalpendra B.; Tonde, Sunil S.; Didgikar, Mahesh R.; Joshi, Sunil S.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2007)
Hydroformylation of 6-methoxy-2-vinylnaphthalene (MVN), using homogeneous Rh(CO)acac) as a catalyst and a chelating bidentate ligand (1,2-bis-(diphenylphosphino) ethane, dppe), followed by oxidation of the product (2-(6-methoxynaphthyl) propanal, 2-MNP) has been studied as an alternative route for the synthesis Of D,L-naproxen. The feasibility of the MVN hydroformylation route has been demonstrated, and a detailed study has been reported on the key hydroformylation step. The roles of the catalyst, ligands, and solvents, as well as the effect of reaction conditions on the reaction rate and regioselectivity of the product 2-MNP, have been investigated. With Rh(CO)2(acac) as a catalyst and dppe as a ligand, > 98% selectivity to 2-MNP (an important precursor to D,L-naproxen) has been achieved. A possible mechanism to explain the variation in regioselectivity with Rh(CO)(2)(acac) as a catalyst and dppe as a ligand has been discussed. The kinetics of the hydroformylation step has been investigated and a rate equation has been proposed. The second step in the proposed route for naproxen-the oxidation of 2-MNP to 2-(6-methoxynaphthyl) propanoic acid (2-MNPA, or naproxen) - has been studied using Na2WO4 as a catalyst and tetrabutyl ammonium hydrogen sulfate (TBAHS) as the phase-transfer catalyst with H2O2 as the oxidant for the first time. Screening of the catalysts that consisted of the early transition metals, such as salts of tungsten, vanadium, and molybdenum showed that Na2WO4 gives the best performance for the oxidation step with > 80% selectivity to 2-(6-methoxynaphthyl)propanoic acid (2-MNPA/naproxen). This study would be valuable in developing a new environmentally benign route for naproxen synthesis.

Immobilized palladium nanoparticles catalyzed oxidative carbonylation of amines - Didgikar, Mahesh R.; Roy, Debdut; Gupte, Sunil P.; Joshi, Sunil S.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2010)
Catalytic application of immobilized palladium nanoparticles for synthesis or ureas by oxidative carbonylation of amines has been investigated. This is the first report oil oxidative carbonylation of amines to ureas using immobilized palladium nanoparticles catalyst. The palladium nanoparticles were immobilized on a NaY zeolite support through 3-aminopropyl-trimethoxysilane (APTS) as anchoring agent. The [Pd]-APTS-Y catalyst along with NaI promoter showed high conversion and selectivity to the desired urea products over several amine compounds including ail example of an aliphatic amine precursor even at 333 K. The immobilized catalyst was easily separated and recycled several times without any loss of activity. The role of different solvents, iodide promoters, iodide to Pd ratio, concentration of substrates, and temperature on the overall yield of the reaction was also investigated.

Oxidative carbonylation of amine using water-soluble palladium catalysts in biphasic media - Didgikar, Mahesh R.; Joshi, Sunil S.; Gupte, Sunil P.; Diwakar, Makarand M.; Deshpande, Raj Madhukar; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2011)
Application of water-soluble palladium catalysts for oxidative carbonylation of aniline to N,N' diphenyl urea (DPU) has been reported. The water-soluble palladium catalysts prepared from sulfonated N-containing ligands were found to be highly stable under reaction conditions and easily recyclable due to insoluble urea product in the reaction medium. This is in contrast to the sulfonated phosphine ligands, which are vulnerable to oxidation under reaction conditions, showing poor activity and stability. Commercially available as well as laboratory synthesized ligands were used for preparing water-soluble palladium catalysts, for oxidative carbonylation of aniline. The best activity was obtained for Pd complex with disodium 2,2'-bipyridine-4,4'-disulfonate (Bipy-DS) ligand. Under optimized conditions Pd(BipyDS)Pd(OAc)(2) catalyst gave TOF of similar to 210h(-1) with aniline conversion of similar to 97% with similar to 91% selectivity for N.N'-diphenyl urea. It was found that the catalyst was easily reusable up to five times, with negligible loss in the catalytic activity. The effect of reaction parameters was investigated and a plausible reaction mechanism has been proposed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Amine; Biphasic catalysis; Carbonylation; Urea; Water-soluble palladium catalyst

Efficient conversion of cellulose to levulinic acid by hydrothermal treatment using zirconium dioxide as a recyclable solid acid catalyst - Joshi, Sunil S.; Zodge, Amit D.; Pandare, Kiran V.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2014)
Conversion of cellulose into platform chemicals is essential for sustainable development of the chemical industry. With this aim, single step hydrothermal conversion of cellulose to industrially important levulinic acid using zirconium dioxide as a catalyst has been investigated. A remarkably high yield (53.9 mol %) of levulinic acid with excellent accountability and total conversion of cellulose has been achieved at 180 degrees C reaction temperature and reaction time of 3 h with 2 wt % of catalyst and 2 g of cellulose. The major products identified were levulinic acid (LA), formic acid (FA), 5-hydroxymethylfurfural (5-HMF), furfural, and humins. Formation of humins during cellulose hydrolysis and dehydration was observed and is also confirmed by NMR and FTIR analysis. The effect of various reaction parameters such as temperature, time, substrate concentration, and catalyst loading on conversion and selectivity has been studied. The catalyst has been regenerated and recycled several times without any loss of activity and selectivity.

Comparative analysis of extractive and pressure swing distillation for separation of THF-water separation - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Computers & Chemical Engineering, 2017)
In the present work, extractive and pressure-swing distillation methods are analyzed in detail through steady state ASPEN Plus simulations to propose the most economic method for separation of equimolar mixture of THF-Water. Various solvents were evaluated and DMSO was identified as the most appropriate solvent, as it gave minimum Total Annual Cost (TAC) for desired purity. In case of pressure swing distillation, various pressure ranges were explored to achieve minimum TAC. Configurations for extractive and pressure swing distillation with heat integration were also worked out. The optimum designs of extractive and pressure swing distillation with and without heat integration were compared on a common basis of feed conditions and purity constraints. Results indicate that TAC of extractive distillation with heat integration is 5.2% less than that of PSD with partial heat integration. (C) 2017 Elsevier Ltd. All rights reserved.

Vapor-liquid equilibrium data for binary mixtures of acetic acid plus anisole, acetone plus anisole, and isopropanol plus anisole at pressure 96.15 kPa - Mali, Nilesh A.; Mali, Pawan K.; Patil, Asmita P.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2017)
In this work, the vapor-liquid equilibrium (VLE) data have been generated at the local atmospheric pressure of 96.15 kPa for the binary systems acetic acid + anisole, acetone + anisole, and isopropanol + anisole. A circulation type apparatus was designed and developed with few modifications in one of the stills proposed in the literature. For the validation of the new apparatus, VLE data were generated for the known system of N,N-DMF + aniline and compared with the literature data. The VLE data, generated in Txy form for all pairs, were found to be consistent through the point-to-point consistency test. Activity coefficient models, Wilson, NRTL, and UNIQUAC, were fitted to these data using an objective function of minimizing the sum of deviation between experimental and calculated total pressures to estimate the binary interaction parameters. The model predictions with estimated parameters were compared with the experimental data and found appropriate.

Isobaric vapor-liquid equilibrium data for binary systems of anisole with methyl acetate, ethyl acetate, n-propyl acetate, and isopropyl acetate at 93.9 kPa - Bhoi, Bharat R.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2018)
The present work reports experimental isobaric vapor-liquid equilibrium data at 93.9 kPa pressure using a dynamic recirculation still for four binary pairs of acetates with anisole. The suitability of the experimental data for modeling was established by performing the Herington area test, Van Ness test, and mean absolute deviation test. Binary interaction parameters necessary for process modeling were derived through the regression of the VLE data for Wilson, NRTL, and UNIQUAC activity coefficient models with a suitable objective function. VLE data in the form of T-x, y plots indicates no formation of azeotropes for all pairs.

Refractive index and vapor-liquid equilibrium data for the binary systems of anisole with xylene isomers at 93.13 kPa - Yadav, Satyajeet S.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2018)
Phase equilibrium behavior of binary systems of anisole with xylene isomers was analyzed experimentally. An apparatus which establishes equilibrium conditions through continuous circulation of equilibrium vapor condensate and equilibrium liquid was used. Experimental data comprising refractive indices of binary mixtures, equilibrium compositions of vapor and liquid, and equilibrium temperature are reported for all binary systems. Thermodynamic consistency of vapor-liquid equilibrium data was established for using the Herington, Van Ness and absolute mean deviation tests. Interaction parameters of activity coefficient models, Wilson, nonrandom two liquid, and universal quasichemical, which are important for accounting nonideal behavior in process modeling, are also estimated through regression of the respective binary VLE data. Although VLE data shows that binary systems are nonazeotropic in nature, a pinch in the T-x,y plot indicates that separation of all binary system using distillation may need a significant number of stages.

Experimental analysis of vapour-liquid phase equilibria for binary systems of diethyl carbonate with methyl, ethyl, isopropyl, n-butyl and isoamyl acetates at 95 kPa - Bhoi, Bharat R.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical Thermodynamics, 2020)
Experimental analysis of vapour-liquid phase equilibrium (VLE) for five binary pairs of diethyl carbonate (DEC) with methyl acetate, ethyl acetate, isopropyl acetate, n-butyl acetate and isoamyl acetate was carried out in this study. VLE data were generated experimentally at local atmospheric pressure of 95 kPa in a glass dynamic recirculation still. Reliability of data was checked with the thermodynamic consistency tests by Van Ness, infinite dilution, pure component and mean absolute deviation test. Experimental data was found to be thermodynamically consistent with all tests and data was regressed with Wilson, NRTL and UNIQUAC activity coefficient models to determine binary interaction parameters. Binary pair of DEC with n-butyl acetate has shown azeotropic behaviour with minimum boiling azeotrope and a close boiling behaviour through-out the composition range. No azeotropic behaviour was observed for the rest of the binary pairs. (c) 2020 Elsevier Ltd.
Keywords: Diethyl carbonate; ethyl acetate; Isobaric; Isopropyl acetate; methyl acetate; VLE

Experimental vapor-liquid phase equilibrium analysis of the binary systems of aniline with xylene isomers at 93.13 kPa - Yadav, Satyajeet S.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2020)
In the present work, vapor-liquid phase equilibrium (VLE) analyses of binary systems of aniline with four isomers of xylene, comprising p-xylene, m-xylene, o-xylene, and ethylbenzene, are reported at 93.13 kPa. The experimental VLE data was generated in a dynamic circulating vapor-liquid, and the data was found thermodynamically consistent using the Van Ness point-to-point consistency test. The experimental VLE data was regressed with the Wilson, NRTL, and UNIQUAC activity coefficient models to obtain the binary interaction parameters. No azeotropic or close-boiling behavior was observed in any of the binary pair, and these pairs were found suitable for separation through a conventional distillation method.

Extractive distillation configuration for nitric acid dehydration using sulfuric acid as a solvent - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Industrial & Engineering Chemistry Research, 2020)
In this work, an extractive distillation configuration for dehydration of nitric acid is proposed with sulfuric acid as a solvent. Thermodynamic modeling of the vapor-liquid equilibrium of binary and ternary systems of nitric acid/water/sulfuric acid is carried out using the electrolyte non-random two-liquid (eNRTL-RK) thermodynamic property method in the Aspen plus process simulator. The model performance is validated by comparing the experimental data with the estimated data by the eNRTL-RK model and is found to be in good agreement. The thermodynamic model is then used for developing a triple-column extractive distillation sequence, comprising a preconcentration column, an extractive distillation column, and a solvent recovery column. The configuration is designed, simulated, and optimized to concentrate dilute nitric acid using sulfuric acid as a solvent to break the nitric acid-water azeotrope. The operating and structural parameters of the distillation configuration are optimized simultaneously with an objective of minimizing the energy consumption and the total annual cost (TAC) of the overall configuration.

Intensified reactive distillation configurations for production of dimethyl ether - Gor, Nikhil K.; Mali, Nilesh A.; Joshi, Sunil S. (Chemical Engineering and Processing-Process Intensification, 2020)
The combustion properties of dimethyl ether (DME) are similar to the conventional fuels; hence it is being used as a promising green energy source. The conventional method of DME production by methanol dehydration is highly energy consuming due to the use of a series of distillation columns. In the present study, an energy efficient reactive distillation configuration is proposed for DME production which leads to higher methanol conversion with less energy requirement as compared to reported configurations. The reactive distillation (RD) and dual reaction zone reactive divided wall column (RDWC) were analyzed using steady state ASPEN simulations. Subsequently, all the design parameters were optimized by sensitivity analysis to minimize the Total Annual Cost (TAC) of the configuration. The results showed that the RD column is more energy efficient than RDWC as it requires 10.68 % less TAC. The proposed RD and dual reaction zone RDWC configurations were found to have less specific energy requirements and less cost per kg of DME than any other configuration reported earlier.
Keywords: Energy efficient configuration; Reactive distillation; Reactive divided wall column; Total annual cost

Selective monoalkylation of hydroquinone in the presence of SO3H-functionalized ionic liquids as catalysts - Bhongale, Priyanka V.; Joshi, Sunil S.; Mali, Nilesh A. (Chemical Papers, 2020)
A process aiming atO-alkylation of hydroquinone (HQ), where ionic liquids (ILs) act as catalyst is objectively described. Five SO3H-functionalized ILs having different cations were prepared and characterized by NMR and FTIR techniques. The acidity and thermal stability of ILs were determined by Hammett function and thermogravimetric analysis (TGA), respectively. The catalytic activity of these ILs were tested forO-alkylation of HQ with methanol in 4-methoxyphenol (4MP) in the presence of small amount of benzoquinone (BQ). The effect of reaction parameters such as temperature, time, catalyst loading and substrate concentration on the conversion of HQ and product distribution was examined and optimized to maximize the yield of 4MP using 1,3-disulfonic acid imidazolium hydrogen sulfate (IL2) catalyst. Maximum yield of desired product 4MP 93.79% was obtained at 338 K temperature, 5.45 x 10(-2) mol HQ, 8.33 x 10(-3) mol BQ, and 10.37 mol% catalyst loading in 120 min reaction time. Single-product formation was observed up to 338 K temperature but higher temperature (above 338 K) and longer reaction time resulted in the formation of 2,4-dimethoxyphenol (24DMP) as a by-product. Catalyst recyclability was also established up to the fifth run which showed no declination in its activity.
Keywords: 4-Methoxyphenol; Benzoquinone; Hydroquinone; ionic liquids; O-alkylation

Effect of CaCl2 and ZnCl2 salts on isobaric vapor-liquid equilibrium in separation of the azeotropic mixture of ethanol plus water - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Fluid Phase Equilibria, 2021)
Present work analyzes potential of calcium chloride (CaCl2) and zinc chloride (ZaCl(2)) salts as entrainer for breaking the minimum boiling azeotrope of ethanol and water. Isobaric vapor-liquid equilibrium (VLE) data for the binary systems of water + ethanol and ternary system of water + ethanol + calcium chloride, and water + ethanol + zinc chloride were measured at a constant pressure of 94.5 kPa. The effect of salts on the relative volatility of ethanol to water as well as on the vapor phase mole fractions of ethanol were also studied experimentally. From the experimental results, it is observed that with addition of salts, the azeotropic point of the ethanol and water system can be eliminated. Salting out effects in case of calcium chloride was more than that zinc chloride salt. The results obtained in this work showed that calcium chloride could be a better choice for separation of the water + ethanol azeotrope. Electrolyte nonrandom two-liquid (eNRTL) model was used to correlate the experimental VLE data. The model prediction with the regressed parameters was found in well agreement with the experimental data. The experimental data obtained in this work was found thermodynamically consistent using van Ness test. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Azeotrope; eNRTL; Ethanol; salts; Vapor-liquid equilibrium; Water

Hydrogen solubility in biphasic liquid reaction mixture of cinnamaldehyde hydrogenation: experimental and mathematical modeling study - Khan, Muzammil Y.; Joshi, Sunil S.; Ranade, Vivek V. (Journal of Chemical Sciences, 2022)
The solubility of hydrogen in the biphasic reaction mixture of cinnamaldehyde hydrogenation at 298 to 353 K has been determined in this work experimentally and by using a thermodynamic model. It is evident from many studies that the addition of extra phase, aqueous KOH as the fourth phase, to the three-phase cinnamaldehyde hydrogenation mixture [gas (hydrogen)-liquid (cinnamaldehyde + toluene)-solid (catalyst)] leads to enhancement of cinnamyl alcohol selectivity to a great extent. Determination of hydrogen solubility in this biphasic (organic-aqueous) reaction mixture is crucial to understand the intrinsic reaction kinetics of this reaction. The solubility of hydrogen was experimentally determined using a pressure drop method and reported in terms of Henry's constant. Firstly, hydrogen solubility was determined in pure components viz. toluene, cinnamaldehyde, and water followed by determination of its solubility in the cinnamaldehyde-toluene mixture, aqueous KOH, and eventually, in the reaction mixture containing the two immiscible liquid phases. The effect of changing concentrations in these mixtures and changing phase holdups in the total reaction mixture on hydrogen solubility was studied. Starting from pure components to the reaction mixture, the hydrogen solubility was predicted using a two-step thermodynamic approach involving regular solution theory and the theory of corresponding states. The solubility predictions from this thermodynamic model will be helpful in the accurate estimation of kinetic parameters.
Keywords: biphasic liquid mixture; gas-liquid-liquid-solid [GLLS]; hydrogen solubility; Hydrogenation; thermodynamic model

Kinetic study on alkylation of hydroquinone with methanol over SO3H functionalized Bronsted acidic ionic liquids - Bhongale, V. Priyanka; Amonkar, Amogh A.; Joshi, Sunil S.; Mali, Nilesh A. (Canadian Journal of Chemical Engineering, 2022)
O-alkylation of a dihydric phenol (i.e., hydroquinone) with methanol in presence of benzoquinone catalyzed by double SO3H functionalized Bronsted acidic ionic liquids (i.e., 1,3-disulphonic acid imidazolium hydrogen sulphate, 1,3-disulphonic acid benzimidazolium hydrogen sulphate, and sulphuric acid) is studied in a batch reactor. The sensitivity of activity and selectivity with reaction time, temperature, speed of agitation, and catalyst loading was examined. The plausible reaction pathways proposed based on the experimental observations and detailed kinetic investigation are performed by assuming a homogeneous reaction phase. The kinetic parameters, such as pre-exponential factor and activation energy, are estimated for both ionic liquids and sulphuric acid by considering all competitive reactions, and comparative results were presented. An extended form of the Arrhenius equation is used to estimate the kinetic parameters for the reaction which showed curvature in lnk against a 1/T plot. The model prediction with the estimated kinetic parameters is in good agreement with the experimental data, which confirmed the model validity in the experimental operating range. It was found that ionic liquid has a potential application in the synthesis of a selective monoalkylated product of hydroquinone. The kinetic analysis performed is found to be useful in the understanding of process behaviour.
Keywords: 4-Methoxyphenol; Hydroquinone; ionic liquids; Kinetic analysis; O-alkylation

Reduction of carbon dioxide to dimethylformamide using ruthenium doped Mg/Al hydrotalcites under supercritical conditions - Chaudhary, Sagar D.; Rahatade, Shardul S.; Joshi, Sunil S.; Mali, Nilesh A. (Journal of CO2 Utilization, 2022)
The utilization of carbon dioxide is one of the developing areas due to its significant contribution to global warming. Reducing carbon dioxide (CO2) to formic acid and its derivatives has gained importance because of its thermodynamic limitations and high industrial demand. In this article, we report the synthesis of dime-thylformamide (DMF) using ruthenium doped Mg/Al calcined hydrotalcite by CO2 hydrogenation in the presence of dimethylamine (DMA). At optimized conditions, complete conversion of dimethylamine was achieved with more than 92% product yield at 170 degrees C and 13 MPa pressure with a reaction time of 6 h. Key catalyst properties were determined using X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), CO2-temper-ature programmed desorption (TPD), H-2 temperature-programmed reduction (TPR) and Fourier transform infrared (FTIR). The determination of surface morphology was carried out using field emission scanning electron microscope (FE-SEM) and high-resolution transmission electron microscopy (HR-TEM). At the same time, the chemical composition was verified by energy-dispersive X-ray (EDS). In addition, kinetic modeling is performed using the two site Langmuir-Hinshelwood-Hougen-Watson model. The regressed kinetic parameters gave an appropriate fit with experimental concentration values and activation energy is calculated as 413 kJ/mol K-1.
Keywords: Dimethylformamide; Hydrogenation; hydrotalcite; Langmuir-Hinshelwood-Hougen-Watson model; Supercritical carbon dioxide

Reusable and efficient polystyrene immobilized ionic liquid catalyst for batch and flow methylation of hydroquinone - Bhongale, V. Priyanka; Joshi, Sunil S.; Mali, Nilesh A. (Catalysis Letters, 2022)
An environmentally benign process for synthesizing 4-methoxyphenol through methylation of hydroquinone using polystyrene immobilized Bronsted acidic ionic liquid is presented. The catalyst has been characterized by several techniques, such as solid-state NMR, FTIR, and XRD. The morphological properties were analyzed through SEM and TEM analysis. The elemental analysis was performed using EDS and XPS techniques. The catalyst was thermally stable up to 603 K, which was confirmed by TGA. The chemical interaction between ionic liquid and polystyrene was confirmed by measuring the glass transition temperature of pure polystyrene and catalyst. The BET analysis was performed to estimate the catalyst's surface area, pore size, and pore volume. The recyclability of the proposed new catalyst was established up to five recycle runs in the batch mode. In addition, continuous flow experiments were conducted to test the catalytic activity in terms of catalyst life span and showed excellent stability up to 20 h. The rapid separation, long-term stability, and efficient recycling of synthesized polymeric catalysts make an excellent alternative to the commonly used homogeneous catalysts for selective O-methylation of hydroquinone reaction. The newly developed continuous process for synthesizing 4-methoxyphenol with 100% selectivity suggests good opportunities to reduce energy consumption, which designates a cost-effective process. [GRAPHICS] .
Keywords: 4-Methoxyphenol; Hydroquinone; O-methylation; Polystyrene immobilized ionic liquid

Subcritical water hydrolysis of N-acetyl-D-glucosamine: hydrolysis mechanism, reaction pathways and optimization for selective production of 5-HMF and levulinic acid - Kulkarni, Sphurti Prakash; Dure, Shital N.; Joshi, Sunil S.; V. Pandare, Kiran; Mali, Nilesh A. (Carbohydrate Research, 2022)
In this study, the subcritical water hydrolysis of N-acetyl-D-glucosamine (NAG), a monomer of abundant renewable marine biopolymer chitin, for production of value-added chemicals is investigated. The enhanced ionization of water at subcritical conditions (200 degrees C; 50-100 bar), provides enough acidity for deacetylation of NAG resulting in 80% yield of acetic acid along with traces of formic acid, lactic acid, glucose, fructose, 5hydroxymethylfurfural (5-HMF),etc. The significant humin formation indicates that the self-condensation and polymerisation of 5-HMF is favored in water at subcritical conditions. A catalyst p-toluenesulfonic acid (p-TsOH) was employed to selectively convert NAG to levulinic acid (LA) via ring opening of 5-HMF previously formed during hydrolysis. The maximum yield of 27.13 +/- 1% and 53.46 +/- 1% of 5-HMF and LA, respectively, was obtained at process conditions optimized using Box-Behnken design coupled with response surface methodology. Subcritical water enables greener conversion of NAG to platform chemicals wherein the selective production can be achieved by tuning the process conditions.
Keywords: 5-Hydroxymethylfurfural; chitin; Glucosamine; levulinic acid; Response surface methodology; Subcritical water

Continuous hydrogenation of cinnamaldehyde: gas-liquid-liquid-solid helical coil reactor - Khan, Muzammil Y.; Joshi, Sunil S.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2023)
The advantages and challenges of using the gas-liquid-liquid-solid(GLLS) hydrogenation system are discussed in this work using the caseof selective hydrogenation of cinnamaldehyde to cinnamyl alcohol (animportant ingredient in the perfume and flavoring industry). The fourphases in this system include gas (hydrogen)-liquid (organic, reactant+ solvent)-liquid (aqueous KOH)-solid (5% Pt/C catalyst). The additionof second liquid phase, i.e., aqueous KOH significantly increasesselectivity toward cinnamyl alcohol compared to the conventional three-phasehydrogenation. The four-phase GLLS reactions were carried out andoptimized in a continuous helical coil reactor. The role of key aspectssuch as gas solubility, kinetics, flow hydrodynamics, axial dispersion,and mass transfer on the performance of a continuous GLLS reactoris presented and discussed in this work. The presented results anddiscussion will be useful for addressing conflicting demands likelong residence time, low axial dispersion, and high mass transfer.The experimental studies and results of the developed mathematicalmodel indicate that the continuous GLLS helical coil reactor outperformsthe batch operation. The production rates (kg day(-1)) of cinnamyl alcohol achieved in continuous operation were at leastdouble in comparison to batch operation, with 32% less consumptionof precious catalyst (per kg of product). The presented results will open up new opportunities for enhancing selectivity and overall performanceof hydrogenations via introducing a second immiscible liquid phaseand designing continuous tubular reactors for the same.